STRATEGI PENGEMBANGAN USAHA TERNAK SAPI POTONG DI DESA TANJUNG KEMALA BARAT KECAMATAN MARTAPURA (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2016)
The research was conducted in the village of Tanjung Kemala Martapura Eastern District of East OKU District with the aim to determine the business development strategies of cattle. The method used in this study is a survey. The total sample of 25 respondents. Where the peasant population of 110 beef cattle and for his cattle population of 650 animals, with criteria based on beef cattle aged 1-2 years old, has a number of cattle over three tails, and the experience of farmers over five years, respondents agent (buyer) 2, animal husbandry 2. Data were analyzed using input-output approach and descriptive analysis. The results obtained by the development strategy is to increase production and quality of livestock, in order to keep prices and demand remain high and cooperating with the government of East OKU District in completing the infrastructure farmers to ranchers can better know the procedures for the care and maintenance of cattle well.